Article THE EXISTENCE OF THE ACEH GOVERNMENT IN REDUCING ACEH'S FOREST DAMAGE: EKSISTENSI PEMERINTAH ACEH DALAM MENGURANGI KERUSAKAN HUTAN ACEH - Nuribadah Nuribadah (Asia-Pacific Journal of Public Policy, 2022)
The role of the Aceh government in reducing forest degradation has not been maximized. It is proven that many disasters still occur, and the bad impact is that ecological disasters are increasing. This research is: how is the existence of the regional government reducing forest destruction in Aceh? How is the coordination of problem-solving carried out by the Aceh government to minimize the damage to Aceh's forests? Researchers used empirical research methods. Primary and secondary legal materials are the main materials, and preliminary data is obtained through interviews. Data analysis was carried out qualitatively. The study results show that the coordination carried out by the Aceh government is monitoring and monitoring, protection, law enforcement, recovery, boundary demarcation, guidelines implementation, policy formulation, and settlement. It is recommended to the Aceh government that the legislative department evaluate various policies and systems of Aceh's forest management by involving the community as subjects and part of the holder of sovereignty over forest area management. There is a need to coordinate the government of Aceh with other agencies and build strong alliances with local civil society groups.